Joints for joints: cannabinoids in the treatment of rheumatoid arthritis. Issue 3 (May 2019) - Lowin, Torsten; Schneider, Matthias; Pongratz, Georg
Abstract : Purpose of review: An increasing number of patients with rheumatoid arthritis (RA) are using cannabis to treat their symptoms, although systematic studies regarding efficacy in RA are lacking. Within this review we will give an overview on the overall effects of cannabinoids in inflammation and why they might be useful in the treatment of RA. Recent findings: Peripherally, cannabinoids show anti-inflammatory effects by activating cannabinoid type 2 receptors (CB2 ) which decrease cytokine production and immune cell mobilization. In contrast, cannabinoid type 1 receptor (CB1 ) activation on immune cells is proinflammatory while CB1 antagonism provides anti-inflammatory effects by increasing β2 -adrenergic signaling in the joint and secondary lymphoid organs. In addition, the nonpsychotropic cannabinoid, cannabidiol (CBD) demonstrated antiarthritic effects independent of cannabinoid receptors. In addition to controlling inflammation, cannabinoids reduce pain by activating central and peripheral CB1, peripheral CB2 receptors and CBD-sensitive noncannabinoid receptor targets. Summary: Cannabinoids might be a suitable treatment for RA, but it is important to target the right receptors in the right place. For clinical studies, we propose a combination of a CB2 agonist to decrease cytokine production, a peripheral CB1 antagonist to prevent detrimental CB1 signaling and to support anti-inflammatory effects of CB2 via activation of β2 -adrenergic receptors and CBD to induce cannabinoid-receptor-independent anti-inflammatory effects.